DTSGUI: A Python Program to Process and Visualize Fiber‐Optic Distributed Temperature Sensing Data. Issue 5 (10th January 2020) - Domanski, Marian; Quinn, Daven; Day‐Lewis, Frederick D.; Briggs, Martin A.; Werkema, Dale; Lane, John W.
Abstract: Fiber‐optic distributed temperature sensing (FO‐DTS) has proven to be a transformative technology for the hydrologic sciences, with application to diverse problems including hyporheic exchange, groundwater/surface‐water interaction, fractured‐rock characterization, and cold regions hydrology. FO‐DTS produces large, complex, and information‐rich datasets. Despite the potential of FO‐DTS, adoption of the technology has been impeded by lack of tools for data processing, analysis, and visualization. New tools are needed to efficiently and fully capitalize on the information content of FO‐DTS datasets. To this end, we present DTSGUI, a public‐domain Python‐based software package for editing, parsing, processing, statistical analysis, georeferencing, and visualization of FO‐DTS data. Abstract : Article impact statement : DTSGUI is a software package with a graphical user interface for processing and visualization of distributed temperature sensing data.